Sleeping Beauties in Theoretical Physics: 26 Surprising Insights - Padmanabhan, Thanu (Springer, 2016)
This book addresses a fascinating set of questions in theoretical physics which will both entertain and enlighten all students, teachers and researchers and other physics aficionados. These range from Newtonian mechanics to quantum field theory and cover several puzzling issues that do not appear in standard textbooks. Some topics cover conceptual conundrums, the solutions to which lead to surprising insights; some correct popular misconceptions in the textbook discussion of certain topics; others illustrate deep connections between apparently unconnected domains of theoretical physics; and a few provide remarkably simple derivations of results which are not often appreciated. The connoisseur of theoretical physics will enjoy a feast of pleasant surprises skilfully prepared by an internationally acclaimed theoretical physicist. Each topic is introduced with proper background discussion and special effort is taken to make the discussion self-contained, clear and comprehensible to anyone with an undergraduate education in physics.